PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN YAMAHA MIO (STUDI PADA KONSUMEN YAMAHA MATARAM SAKTI SEMARANG) - Bramasatya Mahardika Wibisono; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2020)
In the current era of globalization, competition between industries is getting tougher, both similar and unequal industries. Understanding consumer behavior is an important thing that companies must do so that consumers accept the products the company offers. Yamaha as a growing automotive company today certainly has realized the existence of competition. Purchase decision is a stage where consumer actually buys a product offered. Several factors can influence purchasing decisions, including product quality and price. If a product is considered to have better quality compared to competing products, consumers will tend to choose to buy the product. Pricing strategy is very significant in giving value to consumers and influencing the product image, as well as the consumer's decision to buy. This study aims to determine the effect of product quality (X1) and price (X2) on purchasing decisions (Y) of Yamaha Mio at Yamaha Mataram Sakti Semarang. This type of research is explanatory research. The sampling technique uses non-probability and purposive sampling techniques. The number of samples taken was 100 respondents, who were users and buyers of Yamaha Mio at Yamaha Mataram Sakti Semarang. The analysis technique uses validity and reliability test, cross tabulation, correlation coefficient, determination coefficient, simple regression analysis, multiple regression analysis, t test, and F test with the help of IBM SPSS version 21.0.